2021
DOI: 10.1093/ecco-jcc/jjab210
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy Rates did not Decrease in Paediatric- and Adult-Onset Ulcerative Colitis During the Biologics Era: A Nationwide Study From the epi-IIRN

Abstract: Background It is still of debate whether the advent of biologics has been associated with a change in the natural history of ulcerative colitis [UC]. In this nationwide study we evaluated trends of long-term outcomes in all patients diagnosed with UC in Israel during the biologic era. Methods Data in the epi-IIRN cohort were retrieved from the four Israeli Health Maintenance Organizations covering 98% of the population, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…1 However, real-world studies have shown conflicting results regarding the effectiveness of biologics in terms of changing the natural history of disease. [2][3][4][5] This seeming disparity between the more optimistic results of RCTs as compared with real-world data may be explained by the tight disease monitoring in RCTs, but also by the fact that enrolled patients may differ from those seen in daily clinical practice. Eligibility criteria for clinical trials typically aim to maximise internal validity of the study by enrolling a homogenous cohort while excluding more severe and complicated patients who are potentially less likely to respond to the study drug.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, real-world studies have shown conflicting results regarding the effectiveness of biologics in terms of changing the natural history of disease. [2][3][4][5] This seeming disparity between the more optimistic results of RCTs as compared with real-world data may be explained by the tight disease monitoring in RCTs, but also by the fact that enrolled patients may differ from those seen in daily clinical practice. Eligibility criteria for clinical trials typically aim to maximise internal validity of the study by enrolling a homogenous cohort while excluding more severe and complicated patients who are potentially less likely to respond to the study drug.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory randomised control trials (RCTs) conducted in children and adults with inflammatory bowel disease (IBD) have shown that anti‐tumour necrosis factor (TNF) drugs, most notably infliximab and adalimumab, are effective for inducing and maintaining remission in moderate–severe disease, while reducing the rate of hospitalizations and IBD‐related surgeries 1 . However, real‐world studies have shown conflicting results regarding the effectiveness of biologics in terms of changing the natural history of disease 2–5 . This seeming disparity between the more optimistic results of RCTs as compared with real‐world data may be explained by the tight disease monitoring in RCTs, but also by the fact that enrolled patients may differ from those seen in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, none is effective in most patients, let alone the biologic-experienced patients [ 5 ]. In a nationwide study in Israel, colectomy and steroid dependency rates have remained unchanged in patients with UC during the biological era [ 6 ]. The large proportion of primary nonresponders to each molecularly targeted agent may be due to different dominant cytokine levels depending on disease stage and patient characteristics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, corticosteroids still are the mainstay of conventional therapy of IBD patients 5 . However, when this strategy fails, patients are often subjected to intestinal resection to remove the affected gut 6,7 . In turn, surgery can be associated with inevitable complications, which lead to loss of function within the digestive system 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 However, when this strategy fails, patients are often subjected to intestinal resection to remove the affected gut. 6 , 7 In turn, surgery can be associated with inevitable complications, which lead to loss of function within the digestive system. 8 , 9 Therefore, developing new approaches for IBD is urgently needed.…”
Section: Introductionmentioning
confidence: 99%